2007
DOI: 10.2106/jbjs.f.00409
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Osteoclastic Activity on Tendon-to-Bone Healing

Abstract: Osteoprotegerin significantly improves bone formation around the grafted tendon and improves the stiffness at the healing tendon-bone junction in a rabbit model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
61
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 34 publications
2
61
0
Order By: Relevance
“…Increased osteoclastic activities were accompanied by less bone mineral apposition and poor T-B healing. Rodeo et al 10 evaluated the role of osteoclastic bone resorption in T-B healing after ACL reconstruction in rabbit by modulating osteoclastic activities using osteoprotegerin and the receptor activator of nuclear factor-kappa B ligand. Activation of osteoclasts resulted in less peri-graft bone and a decrease of the stiffness of T-B complexes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased osteoclastic activities were accompanied by less bone mineral apposition and poor T-B healing. Rodeo et al 10 evaluated the role of osteoclastic bone resorption in T-B healing after ACL reconstruction in rabbit by modulating osteoclastic activities using osteoprotegerin and the receptor activator of nuclear factor-kappa B ligand. Activation of osteoclasts resulted in less peri-graft bone and a decrease of the stiffness of T-B complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of osteoclasts resulted in less peri-graft bone and a decrease of the stiffness of T-B complexes. 10 Bisphosphonate, an inhibitor of bone resoprtion, has been studied in an attempt to augment T-B healing in bone tunnel. 5,24 Although satisfactory results were shown after systemic administration of bisphosphonates, our histomorphological evaluation implied that local administration, that is, at the posterior and lateral regions of the tibial tunnel, would be more .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trabecular architecture, bone formation, and bone remodeling along the tendon-bone interface were assessed with use of microcomputed tomography (MS-8 Small Specimen Scanner; Enhanced Vision Systems, London, Ontario, Canada) 24,25 . Time-zero analysis was also performed on five specimens to provide a baseline reference for comparison with the control and experimental groups.…”
Section: Micro-computed Tomography Analysismentioning
confidence: 99%
“…In that study, the areas with more motion and osteoclasts also had the slowest graft-to-tunnel healing time, suggesting that increased motion in the early postoperative stages may negatively impact tendon-bone healing. A previous rabbit model of ACL reconstruction also showed that inhibiting osteoclastic activity with osteoprotegerin improved bone formation at the tendon-bone interface as compared with that seen in animals that received RANKL to stimulate osteoclast activity 20 . In contrast to the current study, that study found increased stiffness of the bone-graft-bone construct in the group with osteoclast inhibition, which may be due to the different levels of osteoclast stimulation and inhibition that were brought about by the pharmacological treatments.…”
mentioning
confidence: 91%